Expression 13: "y" equals StartFraction, "a" Over "b" , EndFraction "x"y=abx
13
Expression 14: "y" equals "a" minus "p"y=a−p
equals=
22
14
Expression 15: "x" equals "q"x=q
equals=
3232
15
Expression 16: "x" equals "b"x=b
equals=
3434
16
Expression 17: "y" equals StartRoot, "r" squared minus left parenthesis, "x" minus "b" plus "r" , right parenthesis squared , EndRoot plus "r"y=r2−x−b+r2+r
17
Expression 18: "y" equals negative StartRoot, "r" squared minus left parenthesis, "x" minus "b" plus "r" , right parenthesis squared , EndRoot plus "r"y=−r2−x−b+r2+r
18
Expression 19: "y" equals StartFraction, "a" Over "b" , EndFraction left parenthesis, "x" minus "b" , right parenthesis plus "a" "k"y=abx−b+ak
19
Expression 20: "y" equals negative StartFraction, "b" Over "a" , EndFraction left parenthesis, "x" minus "q" minus "a" "k" , right parenthesisy=−bax−q−ak
20
Expression 21: "y" equals negative StartFraction, "b" Over "a" , EndFraction left parenthesis, "x" minus "b" , right parenthesis plus "d" minus "b" "k"y=−bax−b+d−bk